ABSENCE OF A REGIONAL SURFACE THERMAL HIGH IN THE BAIKAL RIFT; NEW INSIGHTS FROM DETAILED CONTOURING OF HEAT FLOW ANOMALIES - Poort J.; Klerkx J. (My University, 2004)
Heat flow in active tectonic zones as the Baikal rift is a crucial parameter for evaluating deep anomalous structures and lithosphere evolution. Based on the interpretation of the existing datasets, the Baikal rift has been characterized in the past by either high heat flow, or moderately elevated heat flow, or even lacking a surface heat flow anomaly. We made an attempt to better constrain the geothermal picture by a detailed offshore contouring survey of known anomalies, and to estimate the importance of observed heat flow anomalies within the regional surface heat output. A total of about 200 new and close-spaced heat flow measurements were obtained in several selected study areas in the North Baikal Basin. With an outrigged and a violin-bow designed thermoprobe of 2–3-m length, both the sediment temperature and thermal conductivity were measured. The new data show at all investigated sites that the large heat flow highs are limited to local heat flow anomalies. The maximum measured heat flow reaches values of 300–35000 mW/m2, but the extent of the anomalies is not larger than 2 to 4 km in diameter. Aside of these local anomalies, heat flow variations are restricted to near background values of 50–70 mW/m2, except in the uplifted Academician zone. The extent of the local anomalies excludes a conductive source, and therefore heat transport by fluids must be considered. In a conceptual model where all bottom floor heat flow anomalies are the result of upflowing fluids along a conduit, an extra heat output of 20 MW (including advection) is estimated for all known anomalies in the North Baikal Basin. Relative to a basal heat flow of 55–65 mW/m2, these estimations suggest an extra heat output in the northern Lake Baikal of only 5%, corresponding to a regional heat flow increase of 3 mW/m2. The source of this heat can be fully attributed to a regional heat redistribution by topographically driven ground water flow. Thus, the surface heat flow is not expected to bear a signal of deeper lithospheric thermal anomalies that can be separated from heat flow typical for orogenically altered crust (40–70 mW/m2). The new insights on the geothermal signature in the Baikal rift once more show that continental rifting is not by default characterized by high heat flow.
Keywords: Heat flow; Baikal rift; Offshore; Thermal anomalies; Vent model; Advection